Modelling and experiment of buildings thermo-aeraulic behavior according to the level-compactness in Saharan climate conditions. Issue 3 (2nd July 2016) - Bekkouche, Sidi Mohammed El Amine; Benouaz, Tayeb; Hamdani, Maamar; Cherier, Mohamed Kamel; Yaiche, Mohamed Rédha; Benamrane, Noceir
Abstract: A large number of studies of building energy simulation neglect the humidity, or well represented, with a very simplified method. It is for this reason that we have developed a new approach to the description and modelling of multizone buildings in Saharan climate. The concept of the form factor and index compactness "quotient of external walls area and volume of the building" are two of the key elements for analyzing the building geometry. We can introduce it's as validation tools in some cases. In this paper, governing equations of physical phenomena allow to build a model of the thermo-aeraulic behavior. The primary objective is the validation of numerical results able to determine the humidity and temperature in a multizone space. The calculated results were compared with firstly, experimental values, and secondly with simulated results using TRNSYS software. We check if the results change radically for an invariable compactness index. The comparison shows that the found results are to some extent satisfactory. For buildings of similar thermal properties, especially, the used construction materials, the thermal insulation and thermal inertia level, orientation, etc., the result proves that temperature and specific humidity varie slightly when the compactness index is constant.